2021
DOI: 10.1186/s12935-021-01821-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification the ferroptosis-related gene signature in patients with esophageal adenocarcinoma

Abstract: Background Ferroptosis is a recently recognized non-apoptotic cell death that is distinct from the apoptosis, necroptosis and pyroptosis. Considerable studies have demonstrated ferroptosis is involved in the biological process of various cancers. However, the role of ferroptosis in esophageal adenocarcinoma (EAC) remains unclear. This study aims to explore the ferroptosis-related genes (FRG) expression profiles and their prognostic values in EAC. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 38 publications
(32 reference statements)
4
72
0
Order By: Relevance
“…Recently, the prognosis prediction potential of FRGs has been explored in many human cancers. For example, Zhu et al demonstrated the utility of a 4-FRGs model in predicting the prognosis of esophageal adenocarcinoma (38). Zheng et al developed a 12-FRGs model to better predict the prognosis of patients with lower-grade gliomas (39).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the prognosis prediction potential of FRGs has been explored in many human cancers. For example, Zhu et al demonstrated the utility of a 4-FRGs model in predicting the prognosis of esophageal adenocarcinoma (38). Zheng et al developed a 12-FRGs model to better predict the prognosis of patients with lower-grade gliomas (39).…”
Section: Discussionmentioning
confidence: 99%
“…They also generated a genomic–clinicopathological nomogram integrating age, stage, and risk scores and demonstrated high predictive accuracy. Zhu et al ( 22 ) constructed the predictive model composed of four FRGs in esophageal adenocarcinoma, which had good predictive ability (AUC = 0.744). Furthermore, they performed the polymerase chain reaction and IHC validation in clinical specimens to verify significantly different genes expression profiles in esophageal adenocarcinoma and normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by the ROC curves, the nomogram demonstrates high predictive accuracy and sensitivity, especially for the prediction of 5-year survival. Compared to the conventional TNM staging and previously developed ferroptosis-related gene-signature in EAC 44 , the pyroptosis-related gene signature-based nomogram, which integrates gene expression profiles and clinical parameters, more effectively predicts the prognosis of EAC patients. The use of nomogram based on integrated information can facilitate the prediction of prognosis, clinical decision-making and patient counseling 45 .…”
Section: Discussionmentioning
confidence: 99%